A New Class of Potent N-Methyl-D-Aspartate Receptor Inhibitors: Sulfated Neuroactive Steroids with Lipophilic D-Ring Modifications - Kudova, Eva; Chodounska, Hana; Slavikova, Barbora; Budesinsky, Milos; Nekardova, Michaela; Vyklicky, Vojtech; Krausova, Barbora; Svehla, Pavel; Vyklicky, Ladislav (Journal of medicinal chemistry, 2015)
N-Methyl-D-aspartate receptors (NMDARs) are glutamate-gated ion channels that play a crucial role in excitatory synaptic transmission. However, the overactivation of NMDARs can lead to excitotoxic cell damage/death, and as such, they play a role in numerous neuropathological conditions. The activity of NMDARs is known to be influenced by a wide variety of allosteric modulators, including neurosteroids, which in turn makes them promising therapeutic targets. In this study, we describe a new class of neurosteroid analogues which possess structural modifications in the steroid D-ring region. These analogues were tested on recombinant GluN1/GluN2B receptors to evaluate the structure-activity relationship. Our results demonstrate that there is a strong correlation between this new structural feature and the in vitro activity, as all tested compounds were evaluated as more potent inhibitors of NMDA-induced currents (IC50 values varying from 90 nM to 5.4 μM) than the known endogeneous neurosteroid-pregnanolone sulfate (IC50 = 24.6 μM).
Keywords: Steroids; Sulfates; Lipids; lipidy; steroidy; HEK293 Cells; lidé; sírany; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; HEK293 buňky; Humans